Informational barriers and recommendations for patient inclusion in a Brazilian outpatient oncological service - König, Emanuele; Bohn, Patricia Raquel; de Souza Libânio, Cláudia (InfoDesign, 2022)
The paper aims to map informational barriers to promote inclusion and accessibility with safety and autonomy for patients in an outpatient oncological service. We performed an exploratory study through a case study in a Brazilian outpatient oncological service which included non-participant observation. The results were categorized into failures in the signaling of service facilities, lack of alternative communication resources, and lack of accessible communication considering diverse needs. The main barriers observed in the service were mistaking service entrance, verbal call/ written medical requests, and the absence of architectural elements for accessibility. Recommendations were proposed, seeking to include all the diversity of patients, and enabling them to receive information and make their own decisions in the service independently and safely. All the proposed recommendations sought to look at different needs in order to make the service inclusive.